Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 5 - Logarithmic, Exponential, and Other Transcendental Functions - 5.4 Exercises - Page 352: 44



Work Step by Step

$g(t)=e^{-3t^{-2}}$ let u=$-3t^{-2}$ u'=$-6t^{-3}$ $g(u)=e^u$ $g'(u)=u'e^u$ $gā€™(t)=-6t^{-3}e^{-3t^{-2}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.